Professional Competence of Tennis Coaches and Player Coaching Preference in Selected Higher Educational Institutions in Henan Province, China - Yu, Zhengzheng (International Journal of Social Sciences and Public Administration, 2024)
This study examines the competencies of tennis coaches and the coaching preferences of collegiate athletes in Henan Province, China. Drawing on a quantitative research design, the study aims to assess the relationship between coaches' professional competencies and their demographic characteristics, as well as the alignment between these competencies and athletes' coaching preferences. A survey instrument was administered to tennis coaches and student-athletes from five universities in Henan Province. The results reveal key strengths and areas for improvement in tennis coaching, and identify athlete preferences that can inform coach education and training programs. The findings have implications for enhancing coaching quality, athlete development, and the overall effectiveness of tennis programs in higher education.